A Robust Adaptive Control Algorithm for Multimissile Cooperative Formation. (15th March 2022) - Gong, Zheng; Wang, Mingang; He, Jingang; Zhang, Jin
Abstract : To improve the probability of missile coordinated detection, this paper investigates the control method of multimissile cooperative formation. Based on the missile's nonlinear dynamics modeling, the formation control algorithm based on the position of the leader missile (or virtual leader missile) is studied. Meanwhile, considering the influence of the communication time delay, a robust adaptive cooperative controller satisfying the time delay network is designed. The simulation verification result indicates that cooperative formation can be achieved quickly with small velocity and position tracking errors when the missiles are fully connected. Therefore, the multimissile cooperative formation control algorithm designed in this paper can meet the requirements of multimissile coordinated detection, thus improving the missile's cooperative attack capability.